Procedure For Obtaining Doctor’s Medical Services For General Patients At The Mataram University Education Hospital: PROSEDUR PEROLEHAN JASA PELAYANAN MEDIS DOKTER UNTUK PASIEN UMUM PADA RUMAH SAKIT PENDIDIKAN UNIVERSITAS MATARAM - Hukmi, Azizah (Green Engineering Society, 2025)
Abstract. This study aims to describe the procedures for obtaining medical services from doctors for general patients at the Teaching Hospital of the University of Mataram. A teaching hospital plays an important role not only as a healthcare provider but also as a center for education and training for medical personnel. The method used in this research is descriptive qualitative, with data collection techniques including observations and interviews with medical staff and patients. The results show that the service procedure begins with the registration of general patients, consultation scheduling, medical examinations by doctors, and ends with the provision of prescriptions or further referrals. All service stages follow applicable standard operating procedures and prioritize quality and patient safety. Although the system has been functioning relatively well, there are still some challenges, such as long queues and a limited number of specialist doctors. Therefore, improving procedural efficiency and increasing the number of medical personnel are necessary considerations to enhance the quality of services for general patients. Abstrak. Penelitian ini bertujuan untuk menggambarkan prosedur perolehan jasa pelayanan medis oleh dokter bagi pasien umum di Rumah Sakit Pendidikan Universitas Mataram. Rumah sakit pendidikan memiliki peran penting tidak hanya sebagai penyedia layanan kesehatan, tetapi juga sebagai sarana pendidikan dan pelatihan bagi tenaga medis. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif, dengan teknik pengumpulan data melalui observasi dan wawancara kepada petugas medis dan pasien. Hasil penelitian menunjukkan bahwa prosedur pelayanan dimulai dari proses pendaftaran pasien umum, penjadwalan konsultasi, pemeriksaan medis oleh dokter, hingga pemberian resep atau rujukan lanjutan. Seluruh tahapan pelayanan mengikuti standar operasional yang berlaku dan berorientasi pada kualitas serta keselamatan pasien. Meskipun sistem telah berjalan cukup baik, masih terdapat beberapa kendala, seperti antrean panjang dan keterbatasan jumlah dokter spesialis. Oleh karena itu, peningkatan efisiensi prosedur dan penambahan tenaga medis menjadi hal yang perlu dipertimbangkan untuk meningkatkan mutu layanan kepada pasien umum.